2017
DOI: 10.1142/s0219519417500828
|View full text |Cite
|
Sign up to set email alerts
|

THERMAL ANALYSIS IN DRILLING OF EX VIVO BOVINE BONES

Abstract: Bone drilling is a common procedure in Medicine, mainly in traumatology and orthopedic procedure for fractures fixation and in reconstructive surgery. The success of this surgical procedure is dependent on many factors, namely, on heat generation control during the bone drilling. The main concern in bone drilling is the mechanical and thermal damage of the bone induced by inappropriate parameters such as drill speed and feed-rate during the drilling. This study focuses on the temperature generated during drill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Drilling is a very complex machining process, cumulating the effects of cutting and material extrusion 1 . The heat generated is a result of friction between the drill bit and the cutting surface of the drilled hole and bone chips and fragments 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drilling is a very complex machining process, cumulating the effects of cutting and material extrusion 1 . The heat generated is a result of friction between the drill bit and the cutting surface of the drilled hole and bone chips and fragments 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thermocouples allow direct temperature measurements inside the bone, but they detect only a single temperature point and need preparing pilot holes. Infrared thermography detects an overall thermal profile including also the measurement of leaking heat; however, it detects only the surface temperature, without predicting the temperature of the actual drilling site 1,2,6,11 . According to Möhlhenrich et al .’s systematic review, 18 studies used thermocouples, and 7 used thermal cameras of the involved, analyzed studies 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the initial temperature, the higher rate of heat transfers from cement to the bone [9]. Others authors focused on empirical models for the prediction of heat generated using experimental and computational results [10]- [14]. In this paper a two dimensional thermal and transient model based on finite element method was built to predict the temperature field produced by cement polymerization in metastatic bone tumor lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors studied the exothermic reaction of cement polymerization and reported in different publications predictive results regarding the temperature rise and residual stresses using time-dependent polymerization function [2], [4]. Others proposed empirical models for the prediction of heat generated using experimental and numerical tests [3], [5]- [9]. There are studies in the literature that point out thermal necrosis in cortical bone, usually when it reaches a temperature of 47ºC for 1 min [10]- [11].…”
Section: Introductionmentioning
confidence: 99%